2017
DOI: 10.17707/agricultforest.63.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Calcium Carbonate in Anthropogenic Soils on Flysch Deposits From Dalmatia (Croatia) Using Vis-Nir Spectroscopy

Abstract: SUMMARYThis study aimed to evaluate the ability to use Vis-NIR spectroscopy to predict CaCO 3 in the soil and to determine the contribution of the spectral ranges and wavelengths to the prediction. A total of 180 topsoil samples (0-25 cm) of anthropogenic soils derived from Flysch deposits in Dalmatia (Croatia) were analyzed for CaCO 3 and scanned in the laboratory with an ASD FieldSpec spectroradiometer (350-2500 nm). The partial last square regression (PLSR) with leave-one-out cross-validation method was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Visible and near-infrared (Vis-NIR) spectroscopy has been widely applied to agriculture, life science, polymer materials, and other fields [1,2,3] because of its many advantages, including simplicity of operation, no need for sample pretreatment, real-time online monitoring, and great adaptability of the model. It has been shown that Vis-NIR spectroscopy can be used in wood science for the prediction of wood’s physical, chemical, anatomical, and mechanical properties such as moisture content, microfibril angle, bending strength, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Visible and near-infrared (Vis-NIR) spectroscopy has been widely applied to agriculture, life science, polymer materials, and other fields [1,2,3] because of its many advantages, including simplicity of operation, no need for sample pretreatment, real-time online monitoring, and great adaptability of the model. It has been shown that Vis-NIR spectroscopy can be used in wood science for the prediction of wood’s physical, chemical, anatomical, and mechanical properties such as moisture content, microfibril angle, bending strength, etc.…”
Section: Introductionmentioning
confidence: 99%